Analysis of Teacher Strategies for Teaching Writing Skills on Report Text - Abdurrahman, Abdurrahman; Aprianti, Fitri; Sugesti, Ikariya (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2024)
This study aims to find out how English language teachers use strategies in teaching writing skills and how to apply such strategies to class nine at SMPN 1 Sumber. This research uses a qualitative descriptive design. The population and sample in this study is English teachers at SMPN 1 Sumber. English teacher in this research has four meetings observed by the researcher. The instrument in this study uses classroom observations and questionnaires. The instrument is used to find out the strategies used and how English teachers apply strategies in teaching the report text. The results were analyzed and divided into three stages, including Data Reduction, Data Analysis, and Presentation Data. Based on observations conducted during four meetings, the results showed that teachers used several teacing and learning strategies in teaching the report text. The teaching and learning methods there are: Brainstorming, Developing Topic, Drafting and Revising. The learning strategies is Mind Mapping Strategy, PLEASE Strategy, Guided Writing Strategy, Creative Writing Strategy, and Collaborative Writing Strategy. This strategy can make it easier for teachers to motivate students to create report texts, facilitate teachers in the teaching and learning process, as well as the application of appropriate learning methods. Besides, the activities in reporting skills consist of opening activities, core activities, and closing activities.